High-flux nanofiltration membranes tailored by bio-inspired co-deposition of hydrophilic g-C3N4 nanosheets for enhanced selectivity towards organics and salts. Issue 10 (9th August 2019) - Ye, Wenyuan; Liu, Hongwei; Lin, Fang; Lin, Jiuyang; Zhao, Shuaifei; Yang, Shishi; Hou, Jingwei; Zhou, Shungui; Van der Bruggen, Bart
Abstract : NF membranes functionalized through bio-deposition of g-C3 N4 nanosheets have enhanced water permeability, dye retention and salt transmission, showing great potential for sustainable treatment of highly saline textile wastewater. Abstract : Surface modification with advanced nanomaterials ( i.e., 2D nanosheets) can be used to strategically tailor membrane properties, providing improved solute permselectivity to targeted molecules. In particular, 2D graphite-like carbon nitride (g-C3 N4 ) nanosheets are a promising alternative for membrane modification, due to their exceptional physicochemical properties and facile synthesis. Herein, high-flux nanofiltration (NF) membranes were designed using bio-inspired co-deposition of hydrophilic g-C3 N4 nanosheets with a polydopamine (PDA)/polyethylenimine (PEI) layer onto porous ultrafiltration (UF) substrates. The g-C3 N4 nanosheets created additional nanochannels in the PDA/PEI layer to facilitate water molecule transport, resulting in high permeability (28.4 ± 1.2 L m −2 h −1 bar −1 ). Particularly, the bio-inspired layer structure was tailored from the UF to the NF (592 Da) scale by incorporating g-C3 N4 nanosheets, thereby breaking through the permeability–selectivity trade-off effect. The tailored NF membrane enabled ultrahigh retention of three reactive dyes (610–630 Da, >99.3%) and low salt rejection (2.9% for NaCl; 7.6% for Na2 SO4 ), significantly promoting the fractionation of dyes and salts for dye desalination. Additionally, the hydrophilic g-C3 N4 nanosheets with oxygen plasma treatment further enhanced the wettability of the membrane surfaces, resulting in a superior antifouling performance. This study indicates the promise of g-C3 N4 nanosheets to engineer high-flux NF membranes with desirable fractionation performance for sustainable treatment of highly saline wastewater.